The Lions Quest Program in Turkey: Teachers’ Views and Classroom Practices. - Mine Gol-Guven (International Journal of Emotional Education, 2016)
This is a pilot study to explore the classroom implementation of the Lions Quest Program in Turkey. Teachers of first through eighth grades at two elementary schools who applied the program were interviewed about the program and their classroom practices while they were also observed and their classrooms were also observed. Considerable program implementation differences were found within and between the schools. Three main issues were raised in the interviews, namely that the teachers were not clear about whether social emotional learning (SEL) skills should be taught to students as a separate lesson or not; they seemed to doubt whether school personnel should be responsible for SEL implementation; and although they had positive views of the implementation, they underlined that students’ social and emotional wellbeing is dependent on family background and the developing maturity of the child. In conclusion, the teachers expressed positive views about the Lions Quest Program, yet lacked strong opinions about when, where, and by whom the program needed to be included in the curriculum. Limitations, implementation challenges, and implications for SEL in the Turkish context were also identified.